Post-pandemic Socioeconomic Recovery: A Framework of Integrated Recovery Strategies for Severely Affected Economies - Adekola, Paul O.; Nogueira, Helena; Rodrigues, Daniela (European Journal of Applied Sciences, 2024)
COVID-19 might have come and gone but the effects, which are likely to linger for at least a decade, are still here with us. Life must continue which was why most countries looked for post-pandemic recovery strategies. Many countries, especially those which were severely affected, called for high power workshops, seminars and conferences involving government officials, captains of industries, academia and think tanks just to devise strategies to prevent economic paralysis leading to presentation of many recommendations. In a corroborative fashion, the aim of this article was to examine the socio-economic effects of COVID-19 on severely affected economies and to recommend ways those economies can emerge from the effects. We relied on scoping review of relevant documents on COVID-19 in major search engines especially MEDLINE, PubMed, Scopus and others to look for solutions for severely affected economies. The stages involved in selection, inclusion and systematic review of the retrieved documents were guided by the PRISMA guidelines for systematic reviews. After a series of inclusion and exclusion criteria, 31 articles finally met our expectations and were included in the study. We determined severely affected economies as those which depended mainly on tourism (e.g. Moldova, Seychelles, etc.), the top ten countries with the highest casualties (e.g. USA, UK, India, Brazil, Italy, etc.) and the top ten with the highest number of clinically confirmed cases (e.g. USA, UK, Brazil, etc.). Other criteria include those countries which slipped into depression (e.g. USA, Nigeria, etc.) and those with economic fragility prior the outbreak of COVID-19 (most sub-Saharan Africa countries). Having reviewed the articles, we came up with eight integrated recovery strategies for the economic revival of those severely affected economies, such as: collective intelligence and entrepreneurial resilience, prioritizing e-commerce and digital trading, and re-strategizing tourism and transport. It is believed that if aggressively pursued, severely affected economies will emerge stronger after feeling the heat of COVID-19.